Sustainability in the product design: A review of recent development based on LCA - Mahmood, Salwa; Hassan, Mohd Fahrul; Hemdi, Abdul Rahman; Mat Saman, Muhamad Zameri (Science Publishing Corporation, 2018)
In order to achieve sustainable product design process, aspects such of environmental, economic and social should be balanced. This paper discussed on sustainability of product design, conceptual basis of life cycle assessment (LCA), review of LCA at several product design, methodology of proposed framework and discussion on strengths and limitations of LCA. This paper proposed to develop a framework for improving the product design process based on LCA tool. The aims is to calculate potential impact of environment, eco-nomic and social aspects during product design process. For environmental aspects, LCA tool will be used. For economic and social considerations, life cycle costing (LCC) and social life cycle assessment will be applied respectively. At the end, proposed framework are able to help designers to improve product design by considering all sustainability aspects.